2006
DOI: 10.1021/la0605844
|View full text |Cite
|
Sign up to set email alerts
|

Patterned Arrays of Au Rings for Localized Surface Plasmon Resonance

Abstract: In this paper, we examined the characteristic behavior of localized surface plasmon resonances (LSPR) of Au dot and ring arrays in response to the selective binding of biomolecules. To do this, patterned arrays of Au rings and dots with various feature scales were fabricated over large areas by an imprint lithography technique. Our results showed that the LSPR spectra of the Au nanorings exhibited a blue shift with increase in the ring widths and asymptotically converged to those for Au nanodots. This clearly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
87
0
2

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 108 publications
(91 citation statements)
references
References 20 publications
2
87
0
2
Order By: Relevance
“…Кольцевые наноструктуры на основе благородных металлов при-влекают все большее внимание специалистов благодаря тому, что они не только обеспечивают значительное усиление в них локализованного электромагнитного поля за счет возбуждения поверхностных плазмо-нов, но и позволяют реализовать возможность тонкой настройки плаз-монных резонансов за счет вариации размера и формы колец [1][2][3][4]. Такие наноструктуры уже нашли применение в качестве высокоэффек-тивных антенн в поверхностно усиленной спектроскопии (SERS, SEIRA) [5], как ячейки оптических устройств сверхплотного хранения информации [6], как плазмонные волноводы в системах оптической передачи информации [7], а также в биологических и химических сен-сорах [8].…”
Section: Introductionunclassified
See 1 more Smart Citation
“…Кольцевые наноструктуры на основе благородных металлов при-влекают все большее внимание специалистов благодаря тому, что они не только обеспечивают значительное усиление в них локализованного электромагнитного поля за счет возбуждения поверхностных плазмо-нов, но и позволяют реализовать возможность тонкой настройки плаз-монных резонансов за счет вариации размера и формы колец [1][2][3][4]. Такие наноструктуры уже нашли применение в качестве высокоэффек-тивных антенн в поверхностно усиленной спектроскопии (SERS, SEIRA) [5], как ячейки оптических устройств сверхплотного хранения информации [6], как плазмонные волноводы в системах оптической передачи информации [7], а также в биологических и химических сен-сорах [8].…”
Section: Introductionunclassified
“…Такие наноструктуры уже нашли применение в качестве высокоэффек-тивных антенн в поверхностно усиленной спектроскопии (SERS, SEIRA) [5], как ячейки оптических устройств сверхплотного хранения информации [6], как плазмонные волноводы в системах оптической передачи информации [7], а также в биологических и химических сен-сорах [8]. Для создания кольцевых металлических наноструктур, как правило, применяются методы коллоидальной [2], электронной [3] и ионно-лучевой литографии [5], а также химического синтеза [4], бла-годаря которым созданы не только единичные нанокольца различных размеров, геометрии и формы, но и их периодические массивы. Однако использование указанных методов требует применения дорогостояще-го высокотехнологичного оборудования, зачастую недоступного ши-рокому кругу исследователей.…”
Section: Introductionunclassified
“…13 And, the refractive index sensitivity (RIS) of hollow MNPs is higher than the corresponding solid MNPs due to the long wavelength of bonding mode. 12,14 Besides, the surface Raman scatter enhanced factors of single and dimer of hollow MNPs are several times higher than that of corresponding solid MNP dimer. 15 As the RIS of metal circle nano-ring arrays depends on the ring particle structure parameter and the particle distance, different opinions arise.…”
Section: Introductionmentioning
confidence: 99%
“…15 As the RIS of metal circle nano-ring arrays depends on the ring particle structure parameter and the particle distance, different opinions arise. Some experiments indicated that the RIS was proportional to the ratio of outer diameter to ring-width, as the particle distance of arrays and outer diameter of rings were fixed, 14,16 and was also proportional to the ratio of outer diameter to metal film thickness. 16 However, other experiments indicated that the bigger the ring-width, the higher the RIS, but the smaller the LSPR peak wavelength (LSPRPW), when the center diameter of rings and lattice constants of arrays were fixed.…”
Section: Introductionmentioning
confidence: 99%
“…Ring pattern can also be created from a circular structure by the so-called lateral pattern definition or edge-defined technique [9][10][11][12], where the ring was defined on the sidewall of a circular pillar or hole pattern. Closely resembling the traditional edge defined technique, nanoring was fabricated recently by capillary force lithography [13,14], templated electrochemical deposition [15], and nanoskiving [16]. Here we report an alternative approach for the fabrication of ordered array of nanorings over large area.…”
Section: Introductionmentioning
confidence: 99%